The art of Splatoon : the art book with splattitude! - Nintendo of America Inc. (Milwaukie : Dark Horse Books, 2017)
The Art of Splatoon contains 320 inkredible pages of artwork from Nintendo's splash-hit video game, including 2D and 3D illustrations of your favorite characters, maps, concept art, weapon and gear design, storyboards, sketches, hand-drawn comics . . . and that's only an inkling of what's inside. We're not squidding around: this is a must-have for all fans of Splatoon!
Video game tie-in.
Keywords: Computer art; Computerspelen; Nintendo video games -- Pictorial works